Effects of Teriparatide Compared with Risedronate on Recovery After Pertrochanteric Hip Fracture: Results of a Randomized, Active-Controlled, Double-Blind Clinical Trial at 26 Weeks - Aspenberg, Per; Malouf, Jorge; Tarantino, Umberto; García-Hernández, Pedro A; Corradini, Costantino; Overgaard, Søren; Stepan, Jan J; Borris, Lars; Lespessailles, Eric; Frihagen, Frede; Papavasiliou, Kyriakos; Petto, Helmut; et al. (The Journal of bone and joint surgery. American volume, 2016)
BACKGROUND: Osteoporosis drugs might affect fracture-healing. We therefore studied the effects of teriparatide in comparison with risedronate on recovery after pertrochanteric hip fractures. METHODS: The study was a randomized, multicenter, active-controlled, 78-week trial comparing teriparatide (20 μg/day) with risedronate (35 mg/week) initiated within 2 weeks after fixation of a low-trauma pertrochanteric hip fracture (AO/OTA 31-A1 or 31-A2). The main inclusion criteria were a bone mineral density T-score of ≤-2.0 and 25-OH-vitamin D of ≥9.2 ng/mL. During the first 26 weeks, patients received study medication with oral or injectable placebo plus calcium and vitamin D in a double-blinded fashion. Secondary (Timed Up-and-Go [TUG] test, hip pain, Short Form [SF]-36 health status, and safety) and exploratory (radiographic outcomes and ability to walk) 26-week end points are reported. RESULTS: Of the 224 patients who were randomized, 171 (86 teriparatide, 85 risedronate) were included in the analysis. The mean age was 77 ± 8 years, 77% were female, and 26% had a prior history of low-trauma fracture. The teriparatide group completed the TUG test in a shorter time at 6, 12, 18, and 26 weeks (differences of -5.7, -4.4, -3.1, and -3.1 seconds, respectively; p = 0.021 for the overall difference). They also reported less pain on a visual analog scale immediately after the TUG test at 12 and 18 weeks (adjusted absolute differences of 10.6 and 11.9 mm, respectively; p < 0.05). There were no significant between-group differences in the SF-36 score, Charnley hip pain score, ability to walk, or use of walking aids during follow-up. Radiographic healing at 6, 12, and 26 weeks, mechanical failure of the implant (teriparatide, 7; risedronate, 8), loss of reduction (teriparatide, 2; risedronate, 4), and nonunion (0 cases) were not significantly different. Mild hypercalcemia and hyperuricemia were more frequent with teriparatide. CONCLUSIONS: Teriparatide was associated with less pain and a shorter time to complete the TUG test between 6 and 26 weeks compared with risedronate. Other fracture-recovery outcomes were similar. The results should be interpreted with caution as these were secondary end points. LEVEL OF EVIDENCE: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.
Keywords: senioři; dvojitá slepá metoda; teriparatid; senioři nad 80 let; Double-Blind Method; Risedronic Acid; inhibitory kostní resorpce; výsledek terapie; mužské pohlaví; Bone Density Conservation Agents; Aged, 80 and over; Hip Fractures; ženské pohlaví; Humans; hojení fraktur; Bone Density; kostní denzita; kyselina risedronová; fraktury kyčle; Teriparatide; Female; Aged; Treatment Outcome; lidé; Male; Fracture Healing